Predictive value of the systemic immune–inflammation index for outcomes in large artery occlusion treated with mechanical thrombectomy—a single-center study - Ao Qian; Longyi Zheng; Hui He; Jia Duan; Shuang Tang; Wenli Xing (Frontiers in Neurology)
BackgroundThe systemic immune–inflammation index (SII) is a composite and easily available inflammation index, which can quantitatively reflect the degree of inflammation. This study aims to investigate the predictive value of admission SII for outcomes of large artery occlusion treated with mechanical thrombectomy (MT).MethodsThis retrospective study was conducted at Suining Central Hospital, Sichuan, China. Patients were stratified into quartiles based on their SII. The investigating outcomes included hemorrhagic transformation (HT), malignant brain edema (MBE), 90-day functional outcome, and mortality. The adverse function was defined as the modified Rankin Scale (mRS) score > 2 at the 90-day follow-up. Multivariate analysis was performed to explore the relationships between SII and outcomes. In addition, cases (distinguished from the aforementioned patients) treated with MT + mild hypothermia (MH) were also included to elucidate the relationships between SII/MH and outcomes in a new cohort.ResultsA total of 323 patients treated with MT were included. The observed HT, MBE, adverse function, and mortality rates were 31.9, 25.7, 59.4, and 27.9%, respectively. Multivariate analysis demonstrated that heightened SII was significantly related to HT (odds ratio [OR]: 1.061, 95% confidence interval [CI]: 1.035–1.086, p < 0.001), MBE (OR: 1.074, 95% CI: 1.045–1.103, p < 0.001), adverse function (OR: 1.061, 95% CI: 1.031–1.092, p < 0.001), and mortality (OR: 1.044, 95% CI: 1.018–1.070, p = 0.001), after adjusting sex, age, Glasgow Coma Scale (GCS) score at admission, initial National Institutes of Health Stroke Scale (NIHSS) score, baseline Alberta Stroke Program Early Computed Tomography Score (ASPECTS), present HMCAS, occluded vessel region, collateral score and successful revascularization. HT and MBE may partially account for patients with elevated SII’s adverse function and mortality. In addition, with the criterion of baseline ASPECTS ≤ 7, a total of 42 patients treated with MT + MH were enrolled to build up a new cohort combined with 72 patients treated with mere MT. The risk role of SII and protect effect of MH were identified for HT (SII—OR: 1.037, 95% CI: 1.001–1.074; MH—OR: 0.361, 95% CI: 0.136–0.957), MBE (SII—OR: 1.063, 95% CI: 1.019–1.109; MH—OR: 0.231, 95% CI: 0.081–0.653), and mortality (SII—OR: 1.048, 95% CI: 1.011–1.087; MH—OR: 0.343, 95% CI: 0.118–0.994).ConclusionElevated SII was related to HT, MBE, 90-day adverse function, and mortality after MT. The MH may improve prognosis under high inflammation status.